Dysregulation of epicardial adipose tissue in cachexia due to heart failure: the role of natriuretic peptides and cardiolipin. Issue 6 (20th October 2020) - Janovska, Petra; Melenovsky, Vojtech; Svobodova, Michaela; Havlenova, Tereza; Kratochvilova, Helena; Haluzik, Martin; Hoskova, Eva; Pelikanova, Terezie; Kautzner, Josef; Monzo, Luca; Jurcova, Ivana; Adamcova, Katerina; et al.
Abstract: Background: Cachexia worsens long‐term prognosis of patients with heart failure (HF). Effective treatment of cachexia is missing. We seek to characterize mechanisms of cachexia in adipose tissue, which could serve as novel targets for the treatment. Methods: The study was conducted in advanced HF patients ( n  = 52; 83% male patients) undergoing heart transplantation. Patients with ≥7.5% non‐intentional body weight (BW) loss during the last 6 months were rated cachectic. Clinical characteristics and circulating markers were compared between cachectic ( n  = 17) and the remaining, BW‐stable patients. In epicardial adipose tissue (EAT), expression of selected genes was evaluated, and a combined metabolomic/lipidomic analysis was performed to assess (i) the role of adipose tissue metabolism in the development of cachexia and (ii) potential impact of cachexia‐associated changes on EAT‐myocardium environment. Results: Cachectic vs. BW‐stable patients had higher plasma levels of natriuretic peptide B (BNP; 2007 ± 1229 vs. 1411 ± 1272 pg/mL; P  = 0.010) and lower EAT thickness (2.1 ± 0.8 vs. 2.9 ± 1.4 mm; P  = 0.010), and they were treated with ~2.5‐fold lower dose of both β‐blockers and angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers (ACE/ARB‐inhibitors). The overall pattern of EAT gene expression suggested simultaneous activation of lipolysis and lipogenesis in cachexia. Lower ratio between expression levels of natriuretic peptide receptors C and A was observed in cachectic vs. BW‐stable patients (0.47 vs. 1.30), supporting activation of EAT lipolysis by natriuretic peptides. Fundamental differences in metabolome/lipidome between BW‐stable and cachectic patients were found. Mitochondrial phospholipid cardiolipin (CL), specifically the least abundant CL 70:6 species (containing C16:1, C18:1, and C18:2 acyls), was the most discriminating analyte (partial least squares discriminant analysis; variable importance in projection score = 4). Its EAT levels were higher in cachectic as compared with BW‐stable patients and correlated with the degree of BW loss during the last 6 months ( r  = −0.94; P  = 0.036). Conclusions: Our results suggest that (i) BNP signalling contributes to changes in EAT metabolism in cardiac cachexia and (ii) maintenance of stable BW and 'healthy' EAT‐myocardium microenvironment depends on the ability to tolerate higher doses of both ACE/ARB inhibitors and β‐adrenergic blockers. In line with preclinical studies, we show for the first time in humans the association of cachexia with increased adipose tissue levels of CL. Specifically, CL 70:6 could precipitate wasting of adipose tissue, and thus, it could represent a therapeutic target to ameliorate cachexia.